Identifying dissimilarities among global teams while pursuing new product idea generation practices - Kazmi, Syeda Asiya Zenab; Naaranoja, Marja; Kytölä, Juha (Elsevier, 2016)
This study survey has attempted to explore assessment of a European multinational company's new product idea generation potential linked to their industrial teams’ diversified capabilities as well as their work potential. The study is carried out by employing quantitative, supported through qualitative, research methodologies. The aim behind such an evaluation is to identify and compare the differences in work approaches as well as the specialization in each one of the three target global teams (i.e. Norway, Finland, the UK) of a European multi-national organization, linked to the new product idea generation operations. The study results revealed that team working in Finland's office is strong in ‘NPD team climate trends’ with the scores 3.6, the UK office displayed higher scores on ‘strategic thinking trends’ with the scores 3.6 while Norway office location is strong at ‘NPD idea support trends’ with the overall scores of 3.6.
Keywords: Multinational company; diversified capabilities; new product idea support; NPD team climate; strategic thinking; fi=Tuotantotalous|en=Industrial Management|